Supply Chain Analysis of Rice Seeds: Supplier Relationship Management Perspective at Malang Regency, East Java, Indonesia - Dwiastuti, Rini; Isaskar, Riyanti; N., Tri Wahyu; Aprilia, Anisa; S., Putri Budi (International Journal of Social and Local Economic Governance, 2018)
The aim of this research is to analyze supplier relationship management by two schemes of cooperation in rice seeds production, Farmer to Partner Farmers I and Partner Farmers I to Partner Farmers II in terms of qualified supplier selection, supplier integration, and effective procurement process indicators. Determination sampling methods are by multistage sampling and snowball sampling according to the information from BPSB (Seed Overseeing and Certification Agency) which have criteria the biggest rice seed producer and its marketing area is the largest one. Meanwhile, statistic descriptive by depth interview is used in this research to analyze the importance level of indicators in considering relations to rice seed suppliers. These indicators have some sub indicatrs which has been divided into five scales: not at all important,notÂ  important, important enough, important, and very important. Condition in supply chain management among UD ABC, PF I, and PF II has been running well. They all agree that quality supplier selection, supplier integration, and effective procurement process are crucial indicators. Moreover, BPSB should give accompaniment between rice seed firms and their supplier related to fulfilment of rice seed needs.